Pulmonary embolism and bradycardia in a NSCLC patient treated with crizotinib for a rare mutation. (January 2023) - Shi, Yunjing; Qiu, Zeping; Ding, Yongjie; Chen, Yanjia; Zhang, Andi; Jin, Wei
Introduction: Lung cancer is a major global health problem because of its high incidence and mortality. Targeted therapies have transformed treatment of driver-mutated metastatic non-small cell lung cancer (NSCLC). Nevertheless, recent studies demonstrated that cardiovascular disease (CVD) was the second leading cause of mortality in cancer survivors now, management of patients' cardiovascular health during the course of anticancer therapy has become a great challenge faced by the oncologists. Anticancer related cardiovascular (CV) complications are not limited to traditional chemotherapy, but are also increasingly recognized in targeted therapy. Case Report: We present a case of pulmonary embolism (PE) and bradycardia in a 91-year-old NSCLC patient treated with crizotinib for a rare MET Y1003S mutation. To our knowledge, this is the second report to show antitumor response of crizotinib in lung cancer patients with such a rare mutation. However, the patient complained chest tightness and shortness of breath after a month of standard dose crizotinib therapy. Non-invasive examination revealed new onset bradycardia and PE. Management & Outcome: Such clinical manifestations were associated with targeted therapy-related CV toxicity, on which the emerging discipline cardio-oncology focused, and a multidisciplinary investigation and treatment was conducted. Discussion: This case highlights the CV adverse events of novel therapies and the current challenges to be tackled in cardio-oncology.